P.F508del editing in cells from cystic fibrosis patients - Laura Tammaro; Chiara Barriga; Samuele Turrini; Maria Favia; Monica Gallucci; Elena Beccia; Silvia Recchia (Frontiers, 2021)
This study demonstrates the correction of the p.F508del mutation in the CFTR gene using CRISPR/Cas9 in CFTE29o‑ cells and induced pluripotent stem cells derived from cystic fibrosis patients. Editing efficiency was quantified by measuring both NHEJ and HDR frequencies. In CFTE29o‑ cells, NHEJ ranged from 1.25 % to 2.54 % of alleles and HDR reached up to 1.42 %. In patient‑derived iPSCs, NHEJ varied from 5.5 % to 12.13 %, while the best HDR efficiency was 2.38 %. The results reveal that gene editing of the p.F508del mutation via CRISPR/Cas9 is a relatively rare event, suggesting that subsequent cell selection and cultivation are necessary for practical application.,
Keywords: cystic fibrosis; genome editing; CRISPR; CFTR